Comparison of Emergency Medical Services Delivery Performance using Maximal Covering Location and Gradual Cover Location Problems - Mohd Hafiz Azizan; Ting Loong Go; W.A. Lutfi W.M. Hatta; Cheng Siong Lim; Soo Siang Teoh (Institute of Advanced Engineering and Science, 2017)
Ambulance location is one of the critical factors that determine the efficiency of emergency medical services delivery. Maximal Covering Location Problem is one of the widely used ambulance location models. However, its coverage function is considered unrealistic because of its ability to abruptly change from fully covered to uncovered. On the contrary, Gradual Cover Location Problem coverage is considered more realistic compared to Maximal Cover Location Problem because the coverage decreases over distance. This paper examines the delivery of Emergency Medical Services under the models of Maximal Covering Location Problem and Gradual Cover Location Problem. The results show that the latter model is superior, especially when the Maximal Covering Location Problem has been deemed fully covered.